Pengaruh Corporate Social Responsibility (Csr) Terhadap Kualitas Pelaporan Keuangan Pada Perusahaan Pertambangan Minyak Dan Gas Bumi Yang Terdaftar Di Bursa Efek Indonesia - Mita Sari Angraini; Debbi Chyntia Ovami; Murni Dahlena Nasution (CERED Indonesia Institute, 2022)
This study aims to determine the effect of Corporate Social Responsibility (CSR) on the quality of financial reporting in Oil and Gas Mining companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The type of data used in this research is quantitative data. The population of this study is all oil and gas mining companies listed on the Indonesia Stock Exchange and published reports and the sample is 9 Oil and Gas Mining Companies listed on the Indonesia Stock Exchange from 2015–2019. The data collection technique used is a documentation study. Based on the results of the t statistical test, it was obtained that tcount > ttable (2,625 > 2.05) and Sig < 0.05 (0.020 < 0.05), then Ha was accepted and Ho was rejected. Thus, it can be concluded that CSR has a positive and significant effect on the quality of financial reporting in oil and gas mining companies listed on the Indonesia Stock Exchange. This is reinforced by the coefficient of determination of 23.8% while the remaining 76.2% is influenced by other variables.